A Study on Catalytic Conversion of Non-Food Biomass into Chemicals Fusion of Chemical Sciences and Engineering - Yabushita, Mizuho; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
The topic of this thesis is catalytic conversion of non-food, abundant, and renewable biomass such as cellulose and chitin to chemicals. In biorefinery, chemical transformation of polymers to valuable compounds has attracted worldwide interest for building sustainable societies. First, the current situation of this hot research area has been summarized well in the general introduction of the thesis, which helps readers to become familiar with this topic. Next, the author explains high-yielding production of glucose from cellulose by using an alkali-activated carbon as a catalyst, resulting in a yield of glucose as high as 88%, which is one of the highest yields ever reported. The characterization of carbon materials has indicated that weak acid sites on the catalyst promote the reaction, which is markedly different from reported catalytic systems that require strong acids. In addition, the first catalytic transformation of chitin with retention of N-acetyl groups has been developed. The combination of mechanocatalytic hydrolysis and thermal solvolysis enables the production of N-acetylated monomers in good yields of up to 70%. The catalytic systems demonstrated in this thesis are unique in the fields of both chemistry and chemical engineering, and their high efficiencies can contribute to green and sustainable chemistry in the future. Meanwhile, mechanistic studies based on characterization, thermodynamics, kinetics, and model reactions have also been performed to reveal the roles of catalysts during the reactions. The results will be helpful for readers to design and develop new catalysts and reaction systems.
General Introduction -- Hydrolysis of Cellulose to Glucose Using Carbon Catalysts -- Mechanistic Study of Cellulose Hydrolysis by Carbon Catalysts -- Catalytic Depolymerization of Chitin to N-Acetylated Monomers -- Acid-Catalyzed Dehydration of Sorbitol to 1,4-Sorbitan -- General Conclusions -- Appendices.
Keywords: Catalysis; Chemistry, Organic; Catalysis; Organic Chemistry